Studies of anionic reagents for phosphate beneficiation. - Zhang, P.
A multiyear, comprehensive study of flotation reagents used in phosphate beneficiation was conducted. The study involved the evaluation of pure fatty acid compounds, comparison of various anionic collectors and testing of iso-acids. Various C12 to C22 fatty acids were tested as florida phosphate collectors. The saturtaed fatty acids were found to be very poor collectors when using the standard conditioning procedure, whereas the unsaturated C16 to C22 fatty acids showed fair to good phosphate collecting ability. The C18 fatty acids oleic, impure oleic and lineleic and the C20 eicosenoic acid were shown to be the best phosphate collectors. The best flotation results were obtained using Liqro GA tall oil and oleic acid. Four isostearic/iso-oleic acid type fatty acid collectors were compared with a commercial grade oleic acid and with Ligro GA tall oil as phosphate collectors using standard laboratory conditioning and flotation procedures. The most selective collector evaluated was century 1108. a high isostearic acid-type reagent. However, it was concluded that this excellent-performing reagent was too expensive for commercial use. Overall, the most promising reagent was probably century MO-5. This collector is essentially an iso-oleic acid/stearic acid mixture, and it cost much less. This program laid a sound foundation for developing single collector, all anionic flotation processes.
Keywords: Fatty acid compound; Phosphate beneficiation